Developing and Identifying Possibility & Plausibility of E-Government Services Scenarios in Iran by 1404 - Fateme Sghafi; Alireza Aliahmadi; Seyed Sepehr Ghazi Noory; Mansoureh Hourali (Journal of Information Technology Management)
Many documents in the field of e-government services in Iran have been developed and recently approved, but these documents were ignored future trends and scenarios. The aim of research is developing futures scenario of e-government services by 1404. In this study, using the global network business and success factors, the important uncertainties are identified by expert’s opinions. Population is of 50 Iranian e-government experts and futurists. The current research is the compound research. Using questionnaires and analysis of documents and expert panel, the required data are gathered. Validity of the questionnaire assessed using the panel of experts and the Cronbach's alpha was used for validation. With determination of three uncertainty composed of trust, interoperability and world trade market entry according to the expert's views as the main scenario, eight scenarios were extracted. Then, with the help of experts, four scenario with higher degree of feasibility were selected which allows policymakers to deal with the best possible of future situation.